The effect of landscape structure on the distribution of brown hare Lepus europaeus in farmlands of Germany and Poland - Kamieniarz, R. (Springer-Verlag, 2012)
Habitat management should be an important part of the brown hare (Lepus europaeus) conservation, but the habitat requirements of this species are not fully recognised. The aim of our research was to estimate these requirements by analysing the effect of various agricultural landscape structure features on the distribution of hares in five agricultural areas in Germany and Poland. The local density of hares was assessed in the spring and autumn of 2006 by using the method of spotlight–strip counts on 9–15 subareas in each research region. The structure of agricultural landscape has been described for each subarea: the share of grain, other crops and grasses as well as the density of crop edges and uncultivated places with wild vegetation. The density of hares was considerably higher in Germany than in Poland (18.8–48.4 vs. 4.1–9.5 indiv./km(2)). The hare density was positively correlated with non-grain crops in an area, with crop edges in two areas and with wild vegetation without trees in two areas, and negatively correlated with grassfields in two areas. The occurrence of wild vegetation without trees affected the hare density only in the study areas, where this habitat was relatively rare (<3 km/km(2)). It was suggested that proper projects aimed at habitat management for brown hares should be elastic, i.e. the projects should be modified depending on the structure of local landscapes. Moreover, the protection and creation of structures with wild vegetation among cropland seem to be considerable methods of brown hare or generally wildlife conservation; therefore, such measures should be an important part of agro-environmental packages.